Pemberian Madu Murni Dalam Menurunkan Tekanan Darah Pada Lansia Hipertensi - Kharisma Niza N; Sudiarto S; Fida Dyah Puspasari (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Background: Cases of hypertension in Central Java increased by 25.8% from the previous year. Hypertension or commonly known with high blood pressure occurs due to increased pressure blood in arteries continuously exceeding limits normal blood pressure. Hypertension can be caused by increasing age but a factor that is no less important is lifestyle. As a reference, treating hypertension can be done in alternative ways, namely with traditional or herbal medicines, one of which is honey. Purpose: to describe the benefits of giving pure honey in lowering blood pressure in the elderly who have hypertension. Method: this uses the case study method with respondents who have systolic blood pressure of 140-159 mmHg and/or diastolic blood pressure of 90-99 mmHg in grade 1 hypertension. Using instruments, namely, interview sheets and observation sheets. Results: The results of the case study showed that honey can reduce blood pressure in hypertension patients. Conclusion: There is a decrease in blood pressure in the elderly by giving honey in the morning and evening with a dose of 20 ml for 7 days with a pre value of 158/95 mmHg and a post value of 138/90 mmHg.